Pengembangan Karakter Kreatif pada Anak Usia Dini Melalui Pembelajaran Tematik - Titi Anisatul Lalely (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2017)
The purpose of this paper is to describe the development of creative character in early childhood through thematic learning. The character that individual needs is creative. When creative characters are developed since childhood, then in this country there will be many creators who are ready to provide change and creativity. Skills possessed through the creative characters will give another character, such as confident, brave, honest, and etc. The thematic learning contained in curriculum of which 2013 is now as a reference of early child education throughout Indonesia has a positive relevance. Learning materials, media, and methods are very interesting and make children happy. A child's happy psychology will have a positive impact on growth and development. The development of creative character in PAUD Wadas Kelir has different learning concept. Three concepts are given: life skills, nature, and knowledge.